LANGUAGE LEARNING STRATEGIES: THE PROFILE OF TEACHER CANDIDATES LEARNING ENGLISH - Adhitya Agri Astarini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
Numerous research on second/foreign language learning indicates that language learning strategies (LLS) play an influential role in the process of language learning. In this regard, the present paper is a survey report on LLS use by teacher candidates in their second year. The survey was conducted in a teacher education institution (IKIP) in Pontianak involving 125 participants. The data collection instrument was SILL for EFL version by Oxford (1990) with 50 items divided into six different strategies; memory, cognitive, compensation, metacognitive, affective, and social strategies. The participants had to choose from Likert-scale ranging from never or almost never true of me (negative) to always or almost always true of me (positive). The data collected were compared to the classification of SILL frequency by Green & Oxford (1995) to determine the range of frequency of each type of strategies. The result showed that metacognitive and social strategies were frequently used by the participants with the mean 3.56 out of 5. In item-based comparison, item number 39 “I try to relax whenever I feel afraid of English” was found to be the highest and most frequent with 74.40% participants positively used the strategy.